2013
DOI: 10.2174/1875399x01306010009
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Brain Activity is Influenced by Cadence in Cyclists

Abstract: Abstract:The importance of the central nervous system in endurance exercise has not yet been exhaustively investigated because of difficulties in measuring cortical parameters in sport science. During exercise there are a lot of artifacts and perturbations which can affect signal quality of cortical brain activity. The technical developments of surface electroencephalography (EEG) minimize such influences during standardized test conditions on a bicycle ergometer. The aim of this study was to investigate how m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…During the test the workload was held constant at 100% P IANS . The test set-up was identical to Hottenrott et al 4 For the EEG recordings, 32 Ag/AgCl electrodes were mounted to the subjects head with a flexible, breathable EEG cap (ActiCap, BrainVision, Germany) and arranged according to the international 10:20 system. 12 Occipital and temporal electrodes were deactivated, as exercise is known to provoke muscle artifacts at these electrode sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the test the workload was held constant at 100% P IANS . The test set-up was identical to Hottenrott et al 4 For the EEG recordings, 32 Ag/AgCl electrodes were mounted to the subjects head with a flexible, breathable EEG cap (ActiCap, BrainVision, Germany) and arranged according to the international 10:20 system. 12 Occipital and temporal electrodes were deactivated, as exercise is known to provoke muscle artifacts at these electrode sites.…”
Section: Methodsmentioning
confidence: 99%
“…12 Occipital and temporal electrodes were deactivated, as exercise is known to provoke muscle artifacts at these electrode sites. 4 FCz was used as reference and AFz as ground. The active EEG electrodes were filled with SuperVisc gel (EasyCap GmbH, Germany) to reduce impedances below 10 K .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the electroencephalogram (EEG) serves as a practical method to assess brain cortical activity during motion as it does not require the restriction of movements (Reis, Hebenstreit, Gabsteiger, Von Tscharner, & Lochmann, 2014). Therefore, knowledge on the dose-response relationship of acute exercise and brain cortical activity has predominantly been generated by investigating EEG rhythms (Hottenrott, Taubert, & Gronwald, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…48 To completely understand affective and perceptual responses during exercise and central fatigue mechanisms, it is crucial to understand the brain processes involved. [49][50][51] Studies have shown, that changes in brain activity occur secondary to the metabolic changes associated with central fatigue during prolonged exercise [52][53][54] and activity in the frontal cortex is associated with affective 55 and perceptual 49 responses to acute bouts of exercise.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 99%